Enterprise Architecture Modeling of Financial Information Systems Using Zachman Framework - Fajri, Faridiah Aghadiati; Zamzami, Faiz; Siregar, Hilda Octavana (Jurnal Akuntansi dan Bisnis, 2020)
As an emerging country, The Regional Public Service Agency in Indonesia is currently allowed to manage their finances independently. The transformation into a regional public service entity was followed by several consequences, one of which was related to the reporting process to the readiness to be audited by the government external auditor. Information technology is able to facilitate the preparation of financial statements, however, the design of information systems in a bureaucratic environment requires a specific subscription. This design requires defining the architecture of information use. This research resulted in a blueprint with an Enterprise Architecture Planning (EAP) approach as the basis for designing financial information systems. In addition, this research also used the Software Process Improvement (SPI) approach to improve the success of information systems. Information technology becomes a vital requirement considering many demands and obligations of BLUDs in terms of financial reporting and performance. The existence of this Enterprise Architecture Model aims as a bridge between organizational goals and information technology to meet these requirements. The results of this study are blueprints of financial software design, especially for BLUD in the health sector in Indonesia.Sebagai negara berkembang, Badan Layanan Umum Daerah di Indonesia saat ini diizinkan untuk mengelola keuangan mereka secara mandiri. Transformasi menjadi entitas layanan publik daerah diikuti oleh beberapa konsekuensi, salah satunya terkait proses pelaporan hingga kesiapan untuk diaudit oleh auditor eksternal pemerintah. Teknologi informasi mampu memfasilitasi penyusunan laporan keuangan, namun demikian, desain sistem informasi dalam lingkungan birokrasi memerlukan perlakuan khusus. Desain ini membutuhkan pendefinisian arsitektur penggunaan informasi. Penelitian ini menghasilkan cetak biru dengan pendekatan Enterprise Architecture Planning (EAP) sebagai dasar untuk merancang sistem informasi keuangan. Selain itu, penelitian ini juga menggunakan pendekatan Software Process Improvement (SPI) untuk meningkatkan keberhasilan sistem informasi. Teknologi informasi menjadi kebutuhan vital mengingat banyak tuntutan dan kewajiban BLUD dalam hal pencatatan, pelaporan hingga pertanggungjelasan kinerja keuangan. Keberadaan Enterprise Architecture Modeling ini bertujuan sebagai jembatan antara tujuan organisasi dan teknologi informasi untuk memenuhi kebutuhan ini. Hasil penelitian ini adalah cetak biru desain perangkat lunak keuangan, terutama untuk BLUD di sektor kesehatan di Indonesia.